Supporting Family Cargivers / Unterstützung für pflegende Angehörige - Posch-Eliskases Ursula; Rungg Christine; Moosbrugger Markus; Perkhofer Susanne (Sciendo, 2015)
Family caregivers suffer from stress due to the caregiving situation which is negatively associated with health. This review focuses on possibilities of support for the family caregivers. This review was performed by the use of the databases PubMed and PsychINFO with the following keywords in various combinations: stress, chronic stress, burden, family caregiving, family caregiver, coping, intervention. An exclusion criterion was infantile care recipient.